Assessment of Metallic FDM samples using x-ray diffraction (Transactions on Additive Manufacturing Meets Medicine, 2019)
X-Ray Diffraction (XRD) characteristics were observed in additively manufactured metallic samples. Sample ‘coupons’ were printed with fused deposition modeling (FDM) systems. The coupons underwent post-processing steps to purge the polymer binder and sinter remaining metal. XRD analysis was performed to measure the crystallographic nature of printed samples at several stages of fabrication. A determination of grain/crystalite size can also be performed on sintered parts using XRD.